Faunal Composition of Medium- and Large-Sized Mammals in Unclassified Forests along National Highway 4 in Tshopo Province (Democratic Republic of the Congo) - Malekani, André B; Angoyo, Roger A; Ndjoku, Bienvenu N; Bipoo, Moïse A; Masudi, Franck M; Gembu, Guy T; Mukinzi, Jean-Claude I; Nebesse, Casimir M (European Journal of Science, Innovation and Technology, 2026)
The aim of this study was to assess the composition, diversity, and abundance of mammal communities at the three sites (Baboro/Libombo, Bafwakondima, and Dikwa). Field data were collected using the “Recce” reconnaissance walk method, and the analyses focused on species richness, diversity indices, Pielou’s evenness index, the kilometer abundance index (KAI), the Morisita index, and the analysis of indicator species (IndVal). A total of 2,028 indices belonging to several taxonomic groups were recorded, with artiodactyls being the most dominant across all sites. Bafwakondima exhibited the greatest species richness (17 species), the highest diversity (H’=2.32), and the greatest evenness (0.82), indicating a more balanced and ecologically stable community. In contrast, Baboro/Libombo and Dikwa exhibited lower diversity and a more pronounced dominance of certain species. The Morisita index revealed a high similarity between Baboro/Libombo and Dikwa (0.96), while Bafwakondima stood out (0.71). The analysis of indicator species identified several significant species at Bafwakondima, highlighting its ecological importance. Human activities, including hunting, logging, and mining, have been observed at all sites and are likely to influence community structure and species distribution.